(untitled) (Journal of Nobel Medical College, 2025)
Background: Hypertension is a major modifiable risk factor for premature mortality. The 2022 Nepal Demographic and Health Survey report a prevalence of about 20%, yet fewer than 5% of cases are adequately controlled, indicating major gaps in detection and management despite initiatives such as the Hypertension Care Cascade. Evidence from the limited studies in Nepal applying the ACC/AHA 2017 guidelines suggests that lower blood pressure cut-offs improve early identification of individuals at increased cardiovascular risk. Materials and Methods: A rural community-based cross-sectional study was conducted among 357 adults using multistage random sampling. Data were collected using a pre-tested questionnaire. Blood pressure was measured using standard procedures and classified according to the ACC/AHA 2017 guidelines. Results: The prevalence of hypertension was 52.1% (n=186). Among hypertensive participants, 61.3% were aware of their condition, 47.8% were receiving antihypertensive treatment, and 33.9% had controlled blood pressure. Age was significantly associated with hypertension (p=0.048), with a higher prevalence of stage 2 hypertension among those aged >60 years. Educational status showed a significant association (p=0.002), with higher prevalence among individuals with no formal education. Physical inactivity and smoking history (pack-years) were also significantly associated (p=0.040). Hypertension was more common among participants from joint or extended families (p=0.016), those reporting financial inadequacy (p<0.001), and certain occupational groups (p<0.001). Conclusion: This study demonstrates a high prevalence of hypertension as compared to other studies in these settings with low levels of treatment and control. Lack of formal education was significantly associated with high blood pressure category. Socioeconomic, Occupational, lifestyle and behavioural factors were also associated with causation of hypertension.